An Overview of Energy Recovery from Local Slaughterhouse-Based Gallus gallus domesticus Greasy Residues and Latest Applications - Zacharie Merlin Ayissi; Alain Fokoua Fongain; Leonel Tsafack Dongmo; Hossain Nazia; Rhiad Alloune; Innocent Ndoh Mbue; Ruben Mouangue (Journal of Combustion)
Gallus domesticus is one of the world’s most consumed animals, with a significant presence in all parts of the planet. Chicken oil appears to be a credible raw material in the context of alternative energy research. This study focuses on a literature review to highlight the chicken’s energy potential and the application of energy recovery from local slaughterhouse-based Gallus gallus domesticus greasy residues and it is proposed to make biodiesel from the fatty residues of Gallus gallus domesticus. The transesterification reaction takes place at 60°C. Methanol is used in a 1 : 6 oil-to-alcohol mass ratio. Catalysis is carried out with 1% (m/m) potassium hydroxide (KOH). The accepted reaction time under light agitation is 120 minutes. The reaction yield is estimated to be 85.6%, and the biodiesel produced is characterized. The postcharacterization values are consistent with the EN14214 biodiesel standard. Gas chromatography coupled with mass spectrometry reveals the intrinsic composition of the acids derived from the developed biodiesel methyl esters. The latter reveals a predominance of oleic acids with a value of 29.47% and palmitic acids with a value of 29.21%. The viscosity of greasy residues appeared to be relatively high at 69.32 mm/s. The low calorific value is 38775.363 KJ/Kg and the cetane index is 50. It has been observed that, for 1000 g of fat waste, it is possible to extract by cooking 507.807 g of oil, or an extraction yield of 51%. Fatty chicken residues from tropical market areas can be used as a raw material for biofuel development.